Mobile IoT enabled waste bin with remote control / Muhammad Azahan Nafiz Mohd Parid - Mohd Parid, Muhammad Azahan Nafiz (2024)
Waste management describes a set of system and process for monitoring and managing amount of waste throughout its entire waste cycle, from the low of technology until it can disposal efficiently with advanced system and the main crucial of waste management problem is the system of waste management used for every generation is traditional, so it not possible to manage and collect all type waste effectively. The main objectives of this project are to design an automatic waste bin by using Arduino uno as a microcontroller and to develop a user-friendly mobile application by implementing Internet of Things (IoT) technology by including NODEMCU ESP 8266 as a Wi-fi module and Blynk software to remotely control automation waste bin. Furthermore, the development purposes to validate the Mobile IoT-enabled waste bin with remote control performance in real-world environments. This study explained a project that is combined with a microcontroller-based Arduino uno board and is connected to ultrasonic sensors which its function to measure the percentage amount of waste through into bin, and IR sensor is integrated to open the bin’s lid automatically which included mechanism part, servo motor. Then, the movement of bin is controlled and connected with NODEMCU ESP 8266 (Wi-Fi Module) to give self-instruction through mobile application with Blynk app, however they are for input sensors. For the output sensor, such as a servo motor is functioned as the mechanical of opening bin’s lid, an LCD is displayed the percentage of bin’s capacity, and buzzer is triggered a sound when the capacity in the bin is full. The device is controlled its movement by a mobile application, and the lid of the bin opens in response to motion from humans. The future work will be happened is the device's user-friendly interface the smartphone with remote-control capability, and the automation waste bin functionality and its full operation therefore it will ensure a valuable and long-lasting waste management solution in urban environment.